2014
DOI: 10.1039/c3ra44600j
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvent promoted efficient and environmentally benign four-component domino protocol for synthesis of spirooxindoles

Abstract: An efficient and environmentally benign one-pot four-component domino protocol has been presented for the synthesis of structurally diverse spirooxindoles spiroannulated with pyrazolopyrimidophthalazines, indenopyrazolophthalazines, chromenopyrazolophthalazines and indazolophthalazines involving the reaction of phthalic anhydride, hydrazine hydrate, isatins and cyclic diketones/diamides in a deep eutectic solvent (choline chloride : urea: 1 : 2). The present protocol offers some advantages such as operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 79 publications
0
12
0
1
Order By: Relevance
“…Furthermore, a wide range of biodegradable, inexpensive components such as amino acids and sugars can be used to form DESs, 4,5 and it is this flexibility that makes them such an exciting prospect as a green solvent. 2 Indeed, deep eutectic solvents have been proposed as environmentally friendly alternatives for processes including electrodeposition, 6 metal oxide processing, 7 organic synthesis, 8 and the purification and manufacture of biodiesel. 9,10 Perhaps the most commonly studied DESs are derived from mixing choline chloride with urea, ethylene glycol or glycerol (so-called reline, ethaline and glyceline) and it is these systems that have been used to make general observations of the unique supramolecular structure of DES systems.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a wide range of biodegradable, inexpensive components such as amino acids and sugars can be used to form DESs, 4,5 and it is this flexibility that makes them such an exciting prospect as a green solvent. 2 Indeed, deep eutectic solvents have been proposed as environmentally friendly alternatives for processes including electrodeposition, 6 metal oxide processing, 7 organic synthesis, 8 and the purification and manufacture of biodiesel. 9,10 Perhaps the most commonly studied DESs are derived from mixing choline chloride with urea, ethylene glycol or glycerol (so-called reline, ethaline and glyceline) and it is these systems that have been used to make general observations of the unique supramolecular structure of DES systems.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 , 5 ]. Their application in organic synthesis includes synthesis of different heterocycles [ 6 , 7 , 8 , 9 , 10 ], esterification [ 11 ], aldol reactions [ 12 ], halogenation [ 13 ] as well as N -acetylation of amines [ 14 ], synthesis of mercapto quinazolinones [ 15 ], and Schiff bases [ 16 ], all performed by our group. Knoevenagel condensation in deep eutectic solvents has been studied by Keshavarzipour and Tavakol [ 17 ], indicating that DESs could be a very useful tool in this type of condensation.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Rajawat et al 114 reported a variation of this process using phthalic anhydride and isatin in the presence of hydrazine hydrate and several different 1,3-dicarbonyl components (dimedone, barbituric acid, indan-1,3-dione and 4-hydroxycoumarin). Thus, four structurally diverse spirooxindoles (28)(29)(30)(31) were prepared in good to excellent yields using ChCl/urea (1:2) at 80 °C for 20 to 40 min (Scheme 22).…”
Section: Mcr Based On Knoevenagel Condensationmentioning
confidence: 99%